BUILDING CHARACTER-BASED EDUCATION THROUGH KATO NAN AMPEK IN 21st CENTURY LEARNING SKILLS - Taher, Rahma; Darmasyah (Cerdas Proklamator, 2023)
Character education is one of the conscious efforts that helps humans to face the challenges of globalization and to lead to character education in the 21st century learning process. Character education is also a movement that must be carried out in schools with the aim of creating students who have 21st century skills who have good attitudes responsible, caring, honest and fair to the environment around them. kato nan ampek has been one of the teachings of manners in Minangkabau for a long time, while kato nan ampek has given teachings and rules in communicating to opponents who are spoken to, such as between mamak and nephew, between son-in-law and mintuo, and between children to their parents and between older siblings to younger siblings, besides that schools must also be able to develop 21st century character education through a learning process in collaboration with parents of students. If character education through kato nan ampek is implemented from an early age, it can make Indonesian education more quality and able to prepare students who have quality 21st century skills. Long before this, the Minangkabau people had carried out character education through kato nan ampek. Kato nan ampek for the Minangkabau people is used in everyday life and even today it is still firmly held by the Minangkabau people. This study aims to describe character-based education and apply the values of kato nan ampek (four words) in order to achieve national education goals and students who have quality 21st century skills.